2016
DOI: 10.1089/end.2015.0296
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Free-Hand Puncture Technique to Reduce Radiation in Percutaneous Nephrolithotomy Using Ultrasound with Navigation System Under Magnetic Field: A Single-Center Experience in Hong Kong

Abstract: USNS can provide radiation-free guidance for tract creation in PCNL. It is predictable, precise, reliable, and safe. Most importantly, the technique is easy to learn, particularly for urologists who are new to PCNL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In detail, 11 studies were about radiation exposure and associated harms [ [3] , [4] , [5] , [6] , [7] , [8] , 10 , 11 , [14] , [15] , [16] ]; 19 studies analyzed data on flexible or semirigid URS [ 18 , 19 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]; nine studies assessed factors that affect radiation exposure during PCNL [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]; 21 studies evaluated several methods of renal puncture and their effect on radiation [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ]; two studies reported outcomes on tract dilation [ 68 , 69 ] and another two protocols for reduction of radiation during the whole procedure [ 70 , 71 ]. Regarding general measures that should ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In detail, 11 studies were about radiation exposure and associated harms [ [3] , [4] , [5] , [6] , [7] , [8] , 10 , 11 , [14] , [15] , [16] ]; 19 studies analyzed data on flexible or semirigid URS [ 18 , 19 , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]; nine studies assessed factors that affect radiation exposure during PCNL [ [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]; 21 studies evaluated several methods of renal puncture and their effect on radiation [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] ]; two studies reported outcomes on tract dilation [ 68 , 69 ] and another two protocols for reduction of radiation during the whole procedure [ 70 , 71 ]. Regarding general measures that should ...…”
Section: Resultsmentioning
confidence: 99%
“…Another promising category of renal puncture techniques is the use of magnetic fields created in the operating room, which guide needles with sensors to perform a safe and accurate puncture. During the puncture step, the needle is followed with ultrasound [ 64 , 65 ] or guided only by sensors and the position is confirmed using a ureterorenoscope [ 66 ]. Obesity and calyces occupied by large stone burden may impair successful puncture using these methods [ [64] , [65] , [66] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another disadvantage is that the patient anatomy is obtained in 2D. A similar approach was reported by Chau et al [21], who performed 18 PCNL cases using magnetic field-based ultrasound navigation to visualize the position of the needle tract in relation to the target calyx. Puncture was performed freehand without a needle-guiding system attached to the transducer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, new working techniques and work steps must be learned and practiced by the user. The future trend of percutaneous renal access is evolving away from fluoroscopically assisted puncture, to reduce radiation exposure [20]. This could reduce the harmful long-term effects of radiation exposure and make the use of PCNL in pediatric urology [21] safer.…”
Section: Original Articlementioning
confidence: 99%